Identifikasi Pemeliharaan Vertical Garden di Fairmont Sanur Beach Bali - Radinasuari, Ni Luh Putu Ari; Semarajaya, Cokorda Gede Alit; Sukewijaya, I Made (Jurnal Arsitektur Lansekap; Vol.7, No.2, Oktober 2021, 2021)
Maintenance Identification on Vertical Garden at Fairmont Sanur Beach Bali. Fairmont Sanur Beach Bali has a vertical garden with an area of 10 m x 4 m. The Hotel is able to maintain the plant condition. The purpose of this research is to identify the vertical garden maintenance system at the Fairmont Sanur Beach Bali. The research method uses survey and literature study methods. Data collection techniques are observation, interview, and literature study. Data analysis methods with descriptive methods and scoring tables. The results about the identification of vertical garden maintenance systems consist of watering, water disposal system, trimming, fertilizing, replanting plants, media replacement, sanitation, pest and disease control. Watering in 2 hours creating high humidity in the media. The volume of water released is not fully experienced evapotranspiration. The planting media do not experience drought during the day, so the plants keep fresh. In the calculation of plant suitability values, the corresponding values are Hemigraphis alternata. Plants with adequate value are Epipremnum aureum, Asparagus densiflorus, Ananas bracteatus tricolor, Schefflera Arboricola, and Portulaca grandiflora. In the maintenance process requires a fertigation system to facilitate fertilization. The use of automated systems such as timmers will simplify the maintenance and a more scheduled.